Porous Ceramic Sternal Prosthesis Implantation in a 13-Year-Old Patient Presenting with Metastatic Ewing's Sarcoma - Nicolas Mainard; Dyuti Sharma; Damien Fron; Aurélie Mezel; Federico Canavese; Michel Bonnevalle; Eric Nectoux (Georg Thieme Verlag KG, 2022)
Ewing's sarcoma is the second most frequent primary malignant bone tumor in adolescents and young adults. Locations on the thoracic wall represent up to 20% of primary and secondary locations. We present the case of a 13-year-old patient treated with the use of a radiolucency porous bioceramic prosthesis as a sternal replacement for a wide tumor resection in an oncologic context. Focal radiation therapy was not possible due to the high risk of severe myocardial injuries caused by the sternal location of the tumor. The sternum CERAMIL® (I.CERAM, Limoges, France), in porous alumina (Al2O3) has already been implanted into adults in sternal replacement during its invasion by a tumor or its infectious destruction. There were no complication concerning the surgery. The last follow-up at 2 years postoperatively reveals a satisfactory clinical situation with any functional thoracic complaint and nor any functional respiratory symptoms. The porous alumina sternal prosthesis offers a reliable alternative for sternal replacement indications for children in an oncologic context.